2023
DOI: 10.3390/ani13091477
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Valorisation Strategies to Improve Spent Coffee Grounds’ Nutritional Value as an Ingredient for Ruminants’ Diets

Abstract: Lignin in animal diets is a limiting factor due to its low digestibility. This study assessed the effects of thermal or mechanical pre-treatments and enzymatic hydrolysis on spent coffee grounds’ (SCG) nutritional value and digestibility. A first trial studied the effect of thermal pre-treatment and hydrolysis with removal of the liquid part and a second trial studied mechanical pre-treatment and hydrolysis with and without removal of the liquid part. Autoclaving did not improve the enzymatic performance nor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…When the grape stems were not previously washed the enzymatic and alkali-enzymatic hydrolysis, as commented, this reduced the TRS content and of grape stems increased fibre components, leading to a reduced digestibility of the final product compared to control samples (35% and 40% decrease, respectively). San Martin et al (2023) [49] observed the same trend using similar enzymes and spent coffee grounds as substrates. This reduced digestibility was coherent with the reduced SCFA production observed during fermentation, since SCFA are end-products of microbial fermentation [26].…”
Section: Discussionmentioning
confidence: 61%
“…When the grape stems were not previously washed the enzymatic and alkali-enzymatic hydrolysis, as commented, this reduced the TRS content and of grape stems increased fibre components, leading to a reduced digestibility of the final product compared to control samples (35% and 40% decrease, respectively). San Martin et al (2023) [49] observed the same trend using similar enzymes and spent coffee grounds as substrates. This reduced digestibility was coherent with the reduced SCFA production observed during fermentation, since SCFA are end-products of microbial fermentation [26].…”
Section: Discussionmentioning
confidence: 61%
“…In the present study, the proximate analysis showed that SCW has high nutritive value (NDF > 650 g/kg; ADF > 350 g/kg; CP > 120 g/kg). Previously, coffee grounds have been shown to contain high protein, fat and fiber levels, meaning that it can be considered as a feed source for ruminants [21]. Several studies have used coffee pulp and husk as feed for ruminants [13,22].…”
Section: Nutritive Valuementioning
confidence: 99%